Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
x = -1
y = -2
Step-by-step explanation:
To get y by itself:
3x - y = -1
-y = -1 - 3x
y = 1 + 3x
Solve for x with substitution:
2x = 4(1 + 3x) + 6
2x = 4 + 12x + 6
2x = 10 + 12x
-10x = 10
x = -1
Plug the x value into 3x - y = -1
3(-1) - y = -1
-3 - y = -1
-y = 2
y = -2
Answer:
x = -1 and y = -2
Step-by-step explanation:
2x = 4y +6
x = 2y + 3
3(2y+3) - y = -1
6y+9 - y = -1
6y - y = -10
5y = -10
y = -2
2x = 4(-2) + 6
2x = -8 + 6
x = -4 + 3
x = -1
I hope this helps!
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.